Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw dengan Case Method untuk Melatihkan Keterampilan Berkomunikasi Mahasiswa - Defianti, Aprina; Putri, Desy Hanisa (Jurnal Penelitian Pembelajaran Fisika, 2023)
This study aims to describe students' communication skills after participating in learning basic physics courses with the jigsaw type cooperative learning model with the case method. This research is a quasi-experimental study with a posttest only control group design. The population in this study were all students who took basic physics courses. While the samples in this study were two classes of students taken by purposive sampling technique. Each class consists of 20 students. The experimental class was given jigsaw cooperative learning with the case method and the control class was given direct learning with the discussion method. The results showed that the average value of the experimental class students' communication skills was 76.29 in the good category and the control class was 68.71 in the fairly good category. The results of the difference hypothesis test using the Mann-Whitney test show that the u value (110.5) is smaller than the u value in the table (127). Based on these results, it can be concluded that there are differences in the communication skills of students who receive jigsaw cooperative learning with the case method and those who receive direct learning using the discussion method. This shows that the jigsaw type of cooperative learning with the case method can better train students' communication skills.Keywords: cooperative learning model, jigsaw, case method, student communication skills.